2007
DOI: 10.17851/2237-2083.15.1.89-108
|View full text |Cite
|
Sign up to set email alerts
|

Tipos de tarefas e estratégias de comunicação: investigando a validade de narrativas baseadas em tópicos e em figuras

Abstract: This study set up to investigate the validity of different oral tasks, namely topic-based and picture-based narratives, as data elicitation tasks. Our ultimate goal was to examine whether these two types of narratives would impact upon intermediate learners' L2 oral production, regarding their use of communication strategies (CS) during speech performance. Spearman correlational tests were run so as to check for ranking and frequency of the strategies used by participants in each narrative task. Results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…Even if one argues that these task-repetition effects suggested by Bygate only apply for situations in each the very same task is repeated over time, it is plausible to suggest that, although the tasks of the present study had different topics, they were all narratives (retellings of past events) and were supposed to have the same intrinsic characteristics. This claim was corroborated in a very recent study by Prebianca and Silveira (2007) who investigated the validity of the three oral tasks performed by the participants of the present study. Results showed that the frequency of occurrence of CSs in the picture-based narrative was smaller than in the two topic-based narratives.…”
Section: Data Collection and Analysis Data Collection And Analysis Dasupporting
confidence: 88%
“…Even if one argues that these task-repetition effects suggested by Bygate only apply for situations in each the very same task is repeated over time, it is plausible to suggest that, although the tasks of the present study had different topics, they were all narratives (retellings of past events) and were supposed to have the same intrinsic characteristics. This claim was corroborated in a very recent study by Prebianca and Silveira (2007) who investigated the validity of the three oral tasks performed by the participants of the present study. Results showed that the frequency of occurrence of CSs in the picture-based narrative was smaller than in the two topic-based narratives.…”
Section: Data Collection and Analysis Data Collection And Analysis Dasupporting
confidence: 88%